2003
DOI: 10.1214/aos/1059655905
|View full text |Cite
|
Sign up to set email alerts
|

Decompounding: an estimation problem for Poisson random sums

Abstract: Given a sample from a compound Poisson distribution, we consider estimation of the corresponding rate parameter and base distribution. This has applications in insurance mathematics and queueing theory. We propose a plug-in type estimator that is based on a suitable inversion of the compounding operation. Asymptotic results for this estimator are obtained via a local analysis of the decompounding functional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
76
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 18 publications
2
76
0
Order By: Relevance
“…This problem is also interesting in the field of queueing theory to draw inference on the job size distribution when only having access to the workload. Traditionally, a decompounding (as coined by Buchmann and Grübel [6]) method builds a non-parametric estimate of the claim severity distribution based on the observations of the aggregated sums, see for instance van Es et al [39], Coca [7] and Gugushvili et al [18]. The method we propose effectively decompound the random sum but assumes that the jump sizes are driven by a parametric model.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is also interesting in the field of queueing theory to draw inference on the job size distribution when only having access to the workload. Traditionally, a decompounding (as coined by Buchmann and Grübel [6]) method builds a non-parametric estimate of the claim severity distribution based on the observations of the aggregated sums, see for instance van Es et al [39], Coca [7] and Gugushvili et al [18]. The method we propose effectively decompound the random sum but assumes that the jump sizes are driven by a parametric model.…”
Section: Introductionmentioning
confidence: 99%
“…When the summary is the aggregated loss Ψ(n, u) = n i=1 u i , we effectively decompound the random sum. Traditionally, a decompounding method builds a non-parametric estimate of the claim severity distribution based on the observations of the aggregated sums, see Buchmann and Grübel [7] or Bøgsted and Pitts [6]. A popular application is the study of discretely observed compound Poisson processes, see for instance van Es et al [32], Coca [8] and Gugushvili et al [17] where a Bayesian non-parametric approach is used.…”
Section: Introductionmentioning
confidence: 99%
“…random variables. Estimating the distribution of the x n is known as decompounding and has been well-studied [1,2]. In the present paper, decompounding techniques are generalised to the case when G is a noncommutative group.…”
Section: Introductionmentioning
confidence: 99%
“…The classical problem of decompounding arises in the context of these processes. A functional approach to this problem is given by Buchman and Grübel [1]. A characteristic function method is studied by Van Es et al [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation